2012
DOI: 10.3892/or.2012.2145
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity of herbal extracts used for treatment of prostatic disease on head and neck carcinoma cell lines and non-malignant primary mucosal cells

Abstract: Previously, a growth inhibiting effect of PC-Spes on head and neck carcinoma cell lines had been demonstrated. In order to determine the toxic impact of particular herbs in the mixture, we exposed the head and neck cancer cell lines FADU, HLaC79 and its Paclitaxel-resistant subline HLaC79-Clone1 as well as primary mucosal keratinocytes to increasing concentrations of the herbal mixture Prostaprotect, which has a similar formulation as PC-Spes, as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…However, Schmidt et al . () evaluated the cytotoxicity of herbal extracts, G . glabra being one of those, used for treatment of prostatic disease on head and neck carcinoma cell lines and non‐malignant primary mucosal cells, and Yo et al .…”
Section: Resultsmentioning
confidence: 99%
“…However, Schmidt et al . () evaluated the cytotoxicity of herbal extracts, G . glabra being one of those, used for treatment of prostatic disease on head and neck carcinoma cell lines and non‐malignant primary mucosal cells, and Yo et al .…”
Section: Resultsmentioning
confidence: 99%
“…The Asteraceae plant family is the largest plant family known, to date, that has sesquiterpene lactones (SL) as chemical markers (10,11). Some of these lactones have been tested in vitro and in vivo and showed significant anti-T. cruzi activities (12,13).…”
mentioning
confidence: 99%
“…Researchers have evaluated the cytotoxicity of polyphenol molecule extracted from Glycyrrhiza glabra which is used for the treatment of breast and prostate cancer, head and neck cancer cell lines and non‐malignant primary mucosal cells, and against different cancer cell lines such as Immortal Human Keratinocyte (HaCaT), Lung Adenocarcinoma (A549), and Liver Carcinoma (HepG2) cell lines …”
Section: Resultsmentioning
confidence: 99%
“…ROS‐induced development of cancer involves malignant transformation due to DNA mutations and changed gene expression through epigenetic mechanisms which in turn causes the uncontrolled proliferation of cancerous cells . Also, high levels of ROS are observed in various cancerous cells and several accumulating evidence suggest that ROS function as key signaling molecules stimulate different growth‐related responses that finally begin tumorigenesis and angiogenesis . Several studies showed a remarkable role of antioxidant compounds such as medicinal plants and silver nanoparticles in growth inhibition of endometrium and lung, prostate, breast, ovary, and colon cancer cells with removing ROS …”
Section: Resultsmentioning
confidence: 99%